Институционализация рыночной инфраструктуры угольной отрасли - Стариченко, Л.Л.; Фокина, И.В. (Стратегія і механізми регулювання промислового розвитку, 2014)
Исследованы проблемы становления рыночной инфраструктуры угольной промышленности Украины, определены тенденции развития ее элементов, обоснованы предложения, направленные на институциональное обеспечение эффективного функционирования отрасли. Досліджено проблеми становлення ринкової інфраструктури вугільної промисловості України, визначено тенденції розвитку її елементів, обґрунтовано пропозиції, спрямовані на інституційне забезпечення ефективного функціонування галузі. In the article the problem of the formation of market infrastructure Coal Industry of Ukraine, analyzed its basic elements, including: pricing mechanism, import, the order of the state support system royalties for coal mining, banking, insurance. Determined that the further development of market infrastructure requires a conversion of the coal industry in an orderly process with a clear structure and rules of behavior relations. Given the trends in the development of a market infrastructure, justified proposals aimed at ensuring the effective functioning of the institutional sector.To create a competitive coal market should switch to trading on the basis of direct long-term contracts between producers and consumers, and sale of coal to produce nezakontraktovannogo through exchanges. Operator of the wholesale market for coal - State Enterprise " Ukrainian Coal " - it is advisable to convert to industry information and consulting center.Should not exclude the need for import of coal products to the diversification of sources of income and at the same orientation to foreign coal mines owned by Ukrainian corporations. Public policy should not be directed to a permanent restriction of import of coal, and to increase the competitiveness of domestic ugleproizvoditeley. Procedure for granting state subsidies to unprofitable coal enterprises should be reviewed and regulated legislatively light of WTO rules and the EU, on the basis of the principle of equal security companies financially and creating conditions for their equal competition.Procedure for granting state subsidies for retooling mines should be improved in the direction of increasing profitability. Advisable to continue the practice of using borrowed funds, increasing quality requirements developed business plans and economic responsibility of enterprises for the inefficient use of funds.It is advisable that the system of state support for coal mining companies operated in conjunction with the tools of bank lending and insurance (providing cheaper credit capital enterprises, public participation in the process of insurance, etc.). System royalties for coal will become an effective tool for withdrawal of mining rents , creating combined with a system of government subsidies preconditions for equal competition raznorentabelnyh for objective reasons, coal mining enterprises. The fee for the bowels should be differentiated depending not only on the types of minerals , but the natural conditions of their production.